The influence of suspect gender in domestic violence arrests - Truc-Nhu (American journal of criminal justice, 2003)
This study examines heterosexual domestic violence incidents involving male and female suspects. The sample includes 428 incident reports filed at the Columbia (South Carolina) Police Department between 1993 and 1997. Police officers appear to use different arrest determinants for women than for men. The implications of these differential law enforcement practices are discussed.